Retrospective and Comparative Study of Giardia sp. Prevalence in Dogs, Cats, and Small Ruminants in Endemic Areas in Different Brazilian States - Moraes, Livia Fagundes [UNESP]; Kozlowski Neto, Vitoldo Antonio [UNESP]; Oliveira, Raphaela Moreira de [UNESP]; Providelo, Gilson Avelino [UNESP]; Babboni, Selene Daniela; Pinheiro Ferreira, Joao Carlos [UNESP]; Santos Schmidt, Elizabeth Moreira dos [UNESP] (Univ Fed Rio Grande Do Sul, 2019)
Background: Giardia, an intestinal parasite of asexual reproduction, is an important etiologic agent of diarrhea in animals and humans, transmitted by orofecal route. The disease caused by this agent, giardiasis, is endemic in the world and representing an important public health problem. The aim of the present study was do a retrospective study to determine the prevalence of Giardia sp. in fecal samples from dogs, cats, sheep and goats (small ruminants) evaluated at FMVZ Unesp, Botucatu, SP. In addition, this study presents a review of the literature on the prevalence of this protozoan in dogs, cats and small ruminants in different states of Brazil, according to the environmental of these animals. Materials, Methods & Results: During 2011 to 2017, 2,698 fecal samples of dogs, 359 fecal samples of cats and 320 fecal samples of goats and sheep were analyzed. A total of 18.9% of the dogs, 24.8% of the cats, and 6.6% of the goats and sheep were positive for Giardia sp. Only previous studies that used the zinc sulphate centrifugal flotation (Faust technique) were included for comparation of prevalence. The prevalence of Giardia sp. in samples of centrifugation-fluctuation in zinc sulfate was similar in dogs, higher in cats and lower for small ruminants when compared to previous investigations. 4.4% and 6.7% of the positive samples from dogs and cats, respectively, were associated with some co-infection. Co-infections by Cystoisospora spp., Ancylostoma spp. and/ or Toxocara spp. were the most common for dogs and cats. Discussion: This study reveals the presence of Giardia sp. in different animal species in an endemic area. The results are similar to the prevalence previous reported in dogs, and higher in cats using the same diagnostic technique (Faust technique). Co-infections by Cystoisospora spp., Ancylostoma spp. and/ or Toxocara spp. were the most common for dogs and cats, as well-known in previous studies. Investigations with household, shelter and stray dogs found a significantly lower occurrence of Giardia sp. in the group of household dogs. However, for cats these comparisons should made with caution. Despite having a owner, some of these cats have free access to the streets, so they might be more expose to the sources of infection. There are few previous reports of the presence of Giardia sp. in goats and sheep, which presented much higher prevalence when compared with this study. This variation in prevalance of Giardia sp. in small ruminants can occur due to differences inherent to each region in Brazil, as well as the presence of risck factors regarding animal age, type of raising of the animals, hygienic-sanitary and management conditions, and the presence of domestic animals inside sheep and goat installations, which can potentially favor the mechanical transmission of cysts or reservoirs of this parasite. Therefore, due to regional variations in this parasite prevalence, this information is more value in regional areas, reaffirming the importance of this kind of studies in Brazilian states and cities. The intermittent elimination of cysts in feces, the low number of cysts in the samples and asymptomatic infections are relevant points to the diagnosis of giardiasis, making it a challenge. The technique of centrifugation-flotation technique in zinc sulfate gives the best results when compared to other techniques available for the diagnosis of Giardia infections, justifying the choice of this technique by this study. These evidences associated to molecular diagnoses are necessary to determine the real role of these animals in the epidemiology and zoonotic transmission, due to the close contact with humans. This may be considering as a start for further investigations of Giardia sp. at municipality of Botucatu.
Keywords: Giardia sp.; dog; cat; small ruminants; co-infection; shelters and kennel